Quantitative morphological assessment of microvascular network of leiomyoma tissue and the layers of myometrium in patients with uterine leiomyoma with hypo- and hyperestrogenic conditions induced by different schemes of gonadotroping relising hormone agonists therapy - Medvedev M.V. (Морфологія, 2011)
Microvascular components of myomatous tissue and the layers of myometrium were evaluated using mорmorphometric analysis in 35 patients with uterine leiomyoma with long-term and short-term preoperative hormonal correction with Gosereline Acetate. Our results show that the microvessels density depends on morphological type of the fibroid, which in case of the cellular leiomyoma is 2.9 times greater compared to the regular one. The tissue is characterized by decreased vascularization of simple leiomyoma as compared to surrounding myometrium. In conditions of a drug-induced 3-month menopause density of microvessels was significantly decreased. In conditions of elevated levels of sex steroids amount of microvessels in fibrois tissue increases, with expanding of the lumen of arterioles and metarterioles and thickening of their walls. Hipoestrogenic condition contributes significantly to reduction of the average diameter of arterioles in the tissue of cellular and simple leiomyoma, which in some cases leads to complete obliteration of the vessels. Short-time hypere-strogenemia leads to a statistically significant increase in wall thickness of arterioles in fibroid tissue samples. Similar changes observed in vessels of pseudocapsula of women with cellular leiomyoma.